A vida em devir como forma de resistência : etnografia de uma sobrevivência - Kunsler, Alexandre Bosquetti (2018)
Based on an ethnography, carried out over three years, this work seeks to problematize the contours of the contemporary production of desire through the processes of subjectivation that emerge in the encounter of a young person with a set of public policies of social reinsertion, education, and health. These policies were triggered in order to affirm citizenship, constituting new life possibilities after the violent incident that would deeply mark this young man’s trajectory. The possibility of accompanying this resistance in his meetings with the margins of the state, characterized by an intense institutional movement, allowed mapping their assemblages in the composition of existential territories related to the different ways in which the public policies are put before ways of life. Thus, this “Toxic State” produces poisoned relationships, that when the guarantees of citizenship are broken, subjects are positioned as victims of the government, creating the social and subjective conditions for the formation of the territory of the crime.